Peran Guru PAK sebagai Teladan dalam Meningkatkan Kerohanian dan Karakter Peserta Didik - Reni Triposa; Yonatan Alex Arifianto; Yudi Hendrilia (Sekolah Tinggi Teologi Kadesi Yogyakarta, 2021)
The state of the age and its development so rapidly influencing the world become a challenge for students and especially teachers in giving roles and tasks to education especially Christian education. But the role of the teacher in writing that uses library research with a qualitative descriptive approach is expected to improve human resources and bring students to grow in spirituality and character that can build a nation through a person who is strong in relying on God. The Role of Teachers Christian religious education as a role model in enhancing the spirituality and character of learners must be a priority in learning as a form of implying affective values. Teachers as role models in improving the spirituality and character of students, the teacher in this study was asked to have the first responsibility in carrying out the tasks, roles and responsibilities of teachers of Christian religious education. Then the teacher must realize that the Christian Religious Education teacher is an exemplary leader. And then the Master works closely with the church and family to bring about an increase in spirituality and character. And finally the Master must be led by the Holy Spirit.